2018
DOI: 10.4143/crt.2017.512
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Acquired T790M Mutation with Clinical Characteristics after Resistance to First-Line Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor in Lung Adenocarcinoma

Abstract: PurposeThe main objective of this study was to investigate the relationship among the clinical characteristics and the frequency of T790M mutation in advanced epidermal growth factor receptor (EGFR)‒mutant lung adenocarcinoma patients with acquired resistance after firstline EGFR‒tyrosine kinase inhibitor (TKI) treatment.Materials and MethodsWe enrolled EGFR-mutant stage IIIB-IV lung adenocarcinoma patients, who had progressed to prior EGFR-TKI therapy, and evaluated their rebiopsy EGFR mutation status.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 32 publications
8
55
4
Order By: Relevance
“…If clinical application is considered, predicting the emergence of T790M resistance before EGFR TKI treatment is more important and may provide help in tailoring further therapies while the tumour progresses, especially when re-biopsy or liquid biopsy is not feasible. Huang et al reported that longer PFS of first-line TKI and baseline exon 19 deletions were associated with higher frequency acquired T790M mutation [39]. In our analyses, we found that low PD-L1 expression (PD-L1 TPS 0% versus 1e100%) was an independent factor associated with the T790M mutation, after adjusting PFS as a factor.…”
Section: Discussionsupporting
confidence: 48%
“…If clinical application is considered, predicting the emergence of T790M resistance before EGFR TKI treatment is more important and may provide help in tailoring further therapies while the tumour progresses, especially when re-biopsy or liquid biopsy is not feasible. Huang et al reported that longer PFS of first-line TKI and baseline exon 19 deletions were associated with higher frequency acquired T790M mutation [39]. In our analyses, we found that low PD-L1 expression (PD-L1 TPS 0% versus 1e100%) was an independent factor associated with the T790M mutation, after adjusting PFS as a factor.…”
Section: Discussionsupporting
confidence: 48%
“…Huang et al . also found that PFS of more than 11 months was associated with secondary EGFR T790M mutation with an AUC of 0.594 . Since post‐progression use of EGFR TKI is not uncommon, we thought EGFR TKI duration may be more appropriate than EGFR TKI PFS for TKI exposure.…”
Section: Discussionmentioning
confidence: 77%
“…and Huang et al . also reported that those with an EGFR exon 19 deletion were more likely to develop secondary T790M than those with EGFR L858R, as well as uncommon mutations in cohorts with a majority of patients (96% and 94%, respectively) treated with gefitinib or erlotinib . A prior study by Wu et al .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To date, mostly retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and 2 prospective 46,47 Asian case series investigated clinical-pathologic characteristics of T790M mutant lung cancer. Only a few data are available in Caucasian patients, and none of these studies investigated clinical progression patterns related to T790M in detail.…”
Section: Introductionmentioning
confidence: 99%